Emerging Technologies to Treat Heart Disease - Vinall, Maria (MD Conference Express, 2009)
Emerging technologies that address concerns that are not resolved by medication are discussed in this article, including partial circulatory support for medically refractory heart failure patients as well as a low-viscosity polymer that can be used to treat damaged tissue after acute myocardial infarction.